The Effect of Sales Promotion in Social Media on the Students: Purchase Intention of Face Cleaner Water Product - Handy Martinus; Liza Anggraini (Bina Nusantara University, 2018)
The purpose of this research was to determine the effect and the correlation of sales promotion in social media to purchase intention of L’oréal Paris Micellar Water product. The respondents were Binusian (Bina Nusantara students) class of 2013 majoring in marketing communications. The method was the quantitativeexplanatory method. Simple linear regression analysis in SPSS 23 was used to process the data. The results of this research indicate that sales promotion in social media has a significant effect on purchase intention of L’oréal Paris Micellar Water product to the respondents. Moreover, the correlation is positive.